Social and Emotional Learning in the Ibero-American Context: A Systematic Review - Fernández-Martín, Francisco-Domingo; Romero-Rodríguez, José-María; Marín-Marín, José-Antonio; Gómez-García, Gerardo (Frontiers in Psychology, 2021)
Social and emotional learning (SEL) has acquired great prominence in recent years, due to the skills it develops in students, influencing personal and social well-being. At the same time, society is moving towards a model in which understanding oneself and others is a fundamental aspect in order to function properly on a social level. Studies on SEL programmes have been carried out in various parts of the world, although recent reviews have focused exclusively on the Anglo-Saxon context. Therefore, the aim of this paper was to synthesise research on the efficacy and effectiveness of SEL programmes in Ibero-American contexts in early childhood, primary and secondary education. Systematic review was used as the method of enquiry, following the standards of The Campbell Collaboration. In total, 22 empirical studies of SEL programmes implemented in Ibero-America were collected. The results showed that the SEL variables with the highest incidence and significant results were: self-awareness; social awareness; self-control; relationship skills; decision-making; school climate; well-being; and academic achievement. While no studies focused on sense of belonging or school safety. Finally, the establishment of programme components, duration and integration, for each variable, scientifically evidences the keys that can ensure the success of future SEL programmes.